The power of positive thinking - Peale, Norman Vincent (London Vermilion, 2004)
About the bookthe power of positive thinking was birthed due to peale's concern for the pain faced by mankind, providing the readers with tools and techniques to bring about peace of mind. This will enable them to lead a constructive life. The readers are guided into the secrets of positive thinking, which will help them move fast their past failures and achieve the goals they've set.peale throws light on certain techniques that are geared towards preventing readers from accepting defeat over the things that affect their lives. These techniques will also help them experience an improvement in their physical health as well as their energy levels. Peale moves on to talk about individuals who have put these tips into practice and have achieved tremendous results in their lives. He explains that difficulties in life can only impact the well-being of an individual if they're allowed to.the sole reason behind this self-help book is that readers should lead a successful life